2010
DOI: 10.1089/jwh.2009.1880
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Care Among HIV-Infected Pregnant Women in Mississippi

Abstract: Background: Data from the Centers for Disease Control and Prevention (CDC) indicate that reproductive-age black women in the Southeast are disproportionately affected by the HIV epidemic. There are few data describing HIV infection, pregnancies, and follow-up care in this population. Methods: A retrospective chart review was performed at the Perinatal HIV Service at the University of Mississippi Medical Center in Jackson, Mississippi, to identify HIV-infected women 18 years of age with deliveries from 1999 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
4
23
1
Order By: Relevance
“…4 Diagnosis later in pregnancy was associated with a higher likelihood of loss to follow-up, a finding consistent with previous studies. 7,8 In addition to aggressive follow-up of women diagnosed later in pregnancy, there is precedent for antepartum interventions, administered as an adjunct to standard prenatal care, that promote behavior change. For example, a study of screening for diabetes mellitus among women with gestational diabetes reported a significant increase in testing in the 6 months after delivery among women who received an educational intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Diagnosis later in pregnancy was associated with a higher likelihood of loss to follow-up, a finding consistent with previous studies. 7,8 In addition to aggressive follow-up of women diagnosed later in pregnancy, there is precedent for antepartum interventions, administered as an adjunct to standard prenatal care, that promote behavior change. For example, a study of screening for diabetes mellitus among women with gestational diabetes reported a significant increase in testing in the 6 months after delivery among women who received an educational intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our assessment of HIV care outcomes therefore captured encounters with medical care providers even if these encounters occurred at multiple facilities, a limitation of previous clinic-based studies. 7,8 The use of CD4 count and viral load laboratory tests as proxy measures for HIV medical care may limit our ability to evaluate postpartum retention in care and HIV viral suppression because we did not capture medical visits unless a test was ordered. Alternatively, CD4 and viral load tests may overestimate care if they are conducted in the absence of a medical visit.…”
Section: Discussionmentioning
confidence: 99%
“…Even outside the research environment, many women find it difficult to attend doctor visits in the post partum period. Rana et al found that only 37% of women are able to keep two or more visits with their HIV provider during the post partum year (25). In contrast, the women in A5227 were generally presenting for re-treatment well after the first post-partum year.…”
Section: Discussionmentioning
confidence: 99%
“…15 Non-adherence to HIV care postpartum, specifically not attending regular physician appointments, has previously been associated with younger age, initiation of care in the third trimester, more health-related symptoms, discontinuation of ART postpartum psychiatric co-morbidities, and African-American race. 1,3 Postpartum, HIV-infected women are instructed to schedule follow-up visits at 6 weeks following a vaginal delivery and at both 2 and 6 weeks following a Cesareansection. Subsequently, women are asked to resume seeing their primary care provider (PCP) if they are on stable therapy, every 3-6 months.…”
Section: Introductionmentioning
confidence: 99%